Resposta de cultivares de soja à aplicação de foliar silício - CAPRISTO, Denise Prevedel; MENDONÇA, Gabriele Gonçalves de; RODRIGUES, Wagner dos Santo; TORRES, Francisco Eduardo (ANAIS DO ENIC, 2017)
-